Treatment of Cesarean Scar Ectopic Pregnancy with Hysteroscopic Resection - Hoora Amuzegar; Fatemeh Davari Tanha; Firoozeh Akbari Asbagh; Mahbod Ebrahimi; Sareh Ezzati; Venus Hajialiakbar (Gynecology and Minimally Invasive Therapy)
Cesarean scar pregnancy (CSP) is an ectopic that is located in the myometrium of a previous C-section of the scar. It is rare but threatening. The aim of this study was to introduce 10 cases of CSP treated with hysteroscopic resection. In the preoperative phase, the patients with beta-human chorionic gonadotropin (B-hCG) titers more than 10,000 were treated with methotrexate (MTX) to reduce B-hCG titers. Two patients did not receive MTX. All patients were treated with hysteroscopic resection except one patient, who underwent hysteroscopic resectoscopy due to a lack of reduction of B-hCG and due to unrepairable scar site of cesarean and uterine perforation eventuate hysterectomy. All patients had normal menstrual cycles as well as the negative β-hCG level after 2 months. Moreover, no recurrence was reported after 3 years. Low-invasive treatments such as hysteroscopic resection can be an important step to maintain fertility and the general health of patients.